Error propagation and accurate calibration for camera model - Guendouz, B.; Eswaran, C.; Muniandy, S. V (2006)
Error propagation for camera model and the impact of the number of image points on the errors of image coordinates are investigated. The camera calibration process is performed using Mathlab toolbox. The error propagation equations are derived by taldng the appropriate partial derivatives with respect to various measurement errors for image coordinates. Our experiment results show that the error propagation method proposed for image coordinates is accurate enough for most vision systems application and address the problem of engineering intelligent systems.